A Study on Biochemical Composition of the Inner Wall of the Oocyst of Eimeria necatrix - Patra, G.; Rajkhowa, T.K.; Sailo, Lalhruaitluangi; Singh, W. Ramdas; Das, Gunjan; Chanu, Kh. Victoria; Ali, M. Ayub (International Journal of Poultry Science, 2009)
A biochemical study was made to elucidate the biochemical composition of the inner wall of oocyst of Eimeria necatrix and then compared with cellular component of the oocyst. In addition to total protein, glucose and cholesterol, several electrolyte components have been estimated in the present study. The investigation also revealed high activity of Alanine and Asparate aminotransferases in the inner wall of the oocyst of Eimeria necatrix. It seems that the biochemical composition and the enzymes in the inner wall of the oocyst of Eimeria necatrix are of significant value for better metabolic processes in Eimeria spp. as well as for better understanding of possible drug-parasite interaction.